DEVELOPMENT OF INTEGRATED DISCRETE MATHEMATICS TEACHINGBOOK WITH OPS TRANSFORMATION - Ahmad Lazwardi; Mayada Mayada (MATEMATIKA DAN PEMBELAJARAN, 2023)
The Ops Transformation has been analytically proven to be able to solve discrete math problems related to ordinary generating functions. The purpose of this research is to develop a discrete mathematics textbook which has included ops transformation theory as one of its chapters. The research method used is the 4D model research and development method. The results of expert validation on discrete mathematics textbooks equipped with the Ops transformation show that the books are very valid.